Role of the prion protein family in the gonads - Allais-Bonnet, Aurélie; Pailhoux, Eric (Frontiers in Cell and Developmental Biology, 2014)
The prion-gene family comprises 4 members named PRNP (PRPc), PRND (Doppel), PRNT (PRT) and SPRN (Shadoo). According to species, PRND is located 16-52 kb downstream from the PRNP locus, whereas SPRN is located on another chromosome. The fourth prionfamily gene, PRNT, belongs to the same genomic cluster as PRNP and PRND in humans and bovidae. PRNT and PRND possibly resulted from a duplication event of PRND and PRNP, respectively, that occurred early during eutherian species divergence. Although most of the studies concerning the prion-family has been done on PRPc and its involvement in transmissible neurodegenerative disorders, different works report some potential roles of these proteins in the reproductive function of both sexes. Among them, a clear role of PRND, that encodes for the Doppel protein, in male fertility has been demonstrated through gene targeting studies in mice. In other species, Doppel seems to play a role in testis and ovary development but its cellular localization is variable according to the gonadal developmental stage and to the mammalian species considered. For the other three genes, their roles in reproductive function appear ill-defined and/or controversial. The present review aimed to synthesize all the available data on these prion-family members and their relations with reproductive processes, mainly in the gonad of both sexes.